Clinical effects of hypertonic saline boluses in children with severe traumatic brain injury. (23rd August 2021) - Read, Claire; Wignell, Andrew; Stewart, Craig; Davies, Patrick
Abstract : Aim: To quantify the effects of 3% hypertonic saline (HTS) boluses on intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in children. Methods: A retrospective study of patients admitted to a regional neurosurgical children's intensive care unit. Results: A total of 156 HTS boluses were given to children with traumatic brain injury. ICP decreased 6 mmHg ( P  < 0.01) and CPP increased 4 mmHg ( P  = 0.003) 1‐h post‐bolus. Effects persisted for 3 h post‐dose ICP was 5 mmHg lower) and 4 h post‐bolus CPP was 3 mmHg higher. ICP change was not associated with pre‐bolus serum sodium concentration. Conclusions: Hypertonic saline 3% at 5 mL/kg is an effective osmolar therapy for reducing ICP and increasing CPP in children for up to 3 h. '53–53' is a suitable guide – 5 mL/kg of 3% HTS will on average decrease ICP by at least 5 mmHg for 3 h. Pre‐bolus serum sodium concentration is not correlated with effect size.